1998
DOI: 10.1016/s0008-6363(98)00111-4
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Gi-proteins precedes the development of DOCA-salt-induced hypertension: relationship with adenylyl cyclase

Abstract: These results indicate that the enhanced expression of Gi alpha-2 and Gi alpha-3 precedes the development of blood pressure in DOCA-salt-induced hypertension. It can thus be suggested that the increased levels of Gi proteins and resulting decreased levels of cAMP may be one of the factors that contribute to the impaired cardiac contractility and increased vascular tone in DOCA-salt hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
35
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 55 publications
5
35
1
Order By: Relevance
“…6 Furthermore, decreased Gs-protein function has been detected in hypertensive subjects, 29,30 and lower levels of Gs protein have been found in salt-induced hypertensive rats. 31 Upregulation of G␣q/11 and PKC␣ was only found in heart membranes of 2-OHOA-treated rats. Because an increase in cAMP levels as well as signal transduction through G␣q in the heart can lead to higher cardiac contractility via Ca 2ϩ and PKC activation, alterations in the levels of these signaling proteins could be considered a compensatory mechanism to avoid further BP reduction in rats.…”
Section: Discussionmentioning
confidence: 96%
“…6 Furthermore, decreased Gs-protein function has been detected in hypertensive subjects, 29,30 and lower levels of Gs protein have been found in salt-induced hypertensive rats. 31 Upregulation of G␣q/11 and PKC␣ was only found in heart membranes of 2-OHOA-treated rats. Because an increase in cAMP levels as well as signal transduction through G␣q in the heart can lead to higher cardiac contractility via Ca 2ϩ and PKC activation, alterations in the levels of these signaling proteins could be considered a compensatory mechanism to avoid further BP reduction in rats.…”
Section: Discussionmentioning
confidence: 96%
“…Accordingly, deficient AC activity in vascular cells, caused by altered G protein levels and function, diminishes intracellular cAMP levels, a hallmark of hypertension in humans (38,39) and in experimental animal models (30). Indeed, a rise in the expression of inhibitory G i proteins in the aorta of hypertensive animals precedes the development of high BP, which is probably a major contributory factor in the pathogenesis of hypertension (29,30,40,41). In addition, 2-hydroxyoleic acid regulates transient outward K ϩ current in cardiomyocytes, which might be associated with the cardioprotective effects of cis-MUFA (42).…”
Section: Molecular Mechanisms Involved In the Hypotensive Effects Of mentioning
confidence: 99%
“…In turn, this modification affects the docking of important membrane-associated signal transduction proteins involved in controlling BP, such as G proteins (1,24,25). In fact, altered levels and function of G proteins have been reported in both hypertensive humans (26,27) and experimental models of hypertension (28,29).…”
mentioning
confidence: 99%
“…[15][16][17] The increased levels of G i␣ were shown to be associated with hypertension and not with hypertrophy, 21 whereas the decreased levels of G s␣ were associated with hypertrophy and not with hypertension. 22 We have recently shown that the increased expression of G i␣ proteins occurs before the onset of hypertension in SHR 23 and in DOCA-salt hypertensive rats, 24 suggesting that the enhanced levels of G i␣ proteins may be one of the contributing factors in the pathogenesis of hypertension. The present studies were undertaken to investigate the effect of inactivation of G i␣ protein by pertussis toxin (PT) treatment on the development of high BP in SHR.…”
mentioning
confidence: 99%